The Kaca Benggala Model: Revitalizing Javanese Language Learning Through Reflective Digital Pedagogy - Setya Amrih Prasaja; Suwarna; Muhajirin (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2026)
The rapid expansion of digital communication and the growing dominance of global languages have posed significant challenges to the preservation and development of regional languages, including Javanese. This study examines the implementation of the Kaca Benggala Model as a reflective digital pedagogy designed to strengthen students’ awareness of Javanese language identity through systematic comparison with foreign languages. Employing a descriptive qualitative approach grounded in reflective educational practice, the study analyzes learning activities implemented at SMAN 2 Wonosobo, SMAN 1 Sanden, and SMAN 2 Bantul involving 808 students across all grade levels. Data were collected through classroom observations, learning documentation, teacher reflective records, and students’ reflective responses. Data analysis followed qualitative procedures: data reduction, data display, and conclusion drawing. The findings indicate that the Kaca Benggala Model enhanced students’ language awareness, increased learning motivation, strengthened linguistic identity, and transformed perceptions of Javanese language from a traditional school subject into a contemporary cultural resource capable of coexisting with global languages within digital environments. Students demonstrated increased appreciation for the Javanese language and script through the production of digital content. The study concludes that reflective comparison between local and global languages represents an effective pedagogical strategy for regional language revitalization.